Association between chronic diseases and lifestyle risk factors among community-dwelling older adults: a retrospective cross-sectional Chinese population-based study - Xin, Wei; Xu, Dan; Dou, Zulin; Jacques, Angela; Umbella, Josephine; Fan, Yuling; Zhang, Longsheng; Yang, Haiwen; Cai, Hong; Hill, Anne-Marie (Frontiers in Public Health, 2025)
BackgroundChronic diseases among older adults are recognised as a serious public health problem in China, causing rising social and economic burden. The aim of the study was to evaluate the association between chronic diseases and lifestyle risk factors among community-dwelling older adults who attended community health service centres (CHSC) in Southern China.MethodsA retrospective cross-sectional study (n = 361) was conducted using a random sample of cases from a primary care database registry of two CHSC in Guangzhou city, Guangdong province, China. The sample consisted of community-dwelling older adults aged 60 years and over who receive free annual medical examinations provided by the Chinese government. Data collected included biomarkers for chronic diseases, medical history, levels of physical activity, and lifestyle risk factors.ResultsThere were 361 cases [mean age 74.65 (SD = 5.61) years] included in the sample (from total registry records n = 6,351). The top five chronic diseases were hypertension (55.68%), being overweight or obese (43.77%), hyperuricemia (40.60%), fatty liver disease (34.35%) and hypercholesterolemia (17.17%). Being overweight or obese was significantly associated with having fatty liver disease (OR = 1.22, 95% CI 1.05–1.41), higher WC was significantly associated with having hypertension (OR = 1.05, 95% CI 1.02–1.07), hyperuricemia (OR = 1.04, 95% CI 1.01–1.07), dyslipidemia (OR = 1.09, 95% CI 1.03–1.16), and fatty liver disease (OR = 1.22, 95% CI 1.05–1.41). Smoking was significantly associated with having hyperuricemia (OR = 2.40, 95% CI 1.13–5.07).ConclusionData collected via medical examination identified the top five chronic diseases among older adults of Guangzhou city, China. Lifestyle risk factors are significantly associated with chronic diseases. Findings from the study will inform future design and evaluation of targeted, new services for these older adults. Further research to evaluate lifestyle interventions that can improve the health of older adults living with chronic disease is required.Trial registrationEthical approval ([2022]02-014-01) was obtained from the Health Research Ethics Committee of the Third Affiliated Hospital of Sun Yat-Sen University, Guangzhou, China. The study was registered on the Chinese Clinical Trial Registry Centre (registry number: ChiCTR2200066750).